Storage Characteristics and Histamine Content of Fish Stored at Tropical Ambient Temperature - R., Chakrabarti (Fishery Technology, 2025)
During the storage in laboratory, yellow tail scad (Atule mate), seer (Scomberotnorus guttatus), mullet (Mugil cephalus), horse mackerel (Megalaspis cordyla), bull's eye (Priacanthus hamrur), sardine (Sardinella dobsi), long billed half beak (Hemiramphus marginatus), rainbow sardine (Dussumieria acuta) and scad (Scomberoides tol) were found to be organoleptically acceptable up to 4-6 h in winter (20-30oC). However, yellow tail scad, seer, mullet, bull' s eye, black pomfrets (Parastromateus niger) and silver bellies (Leiognathus dussumieri) stored in summer (26-330C) were acceptable up to 4 h only. In summer, the histamine level in all acceptable fish was below 15.0mg.100g"1 muscle which is below maximum admissible limit of 20.0mg.100g"1 muscle. The histamine values in winter days in fish was below ll.0mg.100g"1 muscle, except for long billed half beak. Histamine formation in seer, bull's eye, scad and long billed half beak was more rapid compared to other species under study. Peroxide value in fresh fish such as yellow tail scad, mullet, horse mackerel, scad and silver bellies was nil. An increasing trend in both peroxide value and total volatile base nitrogen (TVBN) was noticed in all samples stored at ambient temperature. TVBN values in organoleptically acceptable fish were between 7.2 and 20.6 mg%.